Criteria for rapidly incorporating online instruction into traditionally in-person programs: a case study - Samsa, Greg; Grambow, Steven (Advances in Social Sciences Research Journal, 2020)
Given the continuing uncertainty about the COCID-19 pandemic, we are planning for the possibility that, in the upcoming semester, some or all of the content of a Master of Biostatistics program will be delivered online. In order to help make this rollout as systematic as possible, we propose criteria which an effective online-enabled educational program should meet. We will incorporate online instruction into our program when: (1) it is necessary and/or educationally beneficial; (2) it can be delivered with sufficient technical quality; (3) instructors have been trained to deliver it sufficiently well; (4) both content and delivery undergo regular review; and (5) policies are in place to support online instruction. These criteria are not unique to graduate programs in biostatistics and, thus, we are presenting this short report and case study in the hope that it will be beneficial to others as they consider and/or prepare for transition to online instruction.